Editorial: Empowerment COVID-19 Prevention during Practicum Courses among Undergraduate Nursing Students - Partuma Rithpho; Sirikanok Klankhajhon (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Editorial: Empowerment COVID-19 Prevention during Practicum Courses among Undergraduate Nursing Students